The factors affecting perceived organizational effectiveness the Sangguniang Kabataan Experience in Iloilo City (November 2007-November 2010). - Clavesillas, John Christopher V.
This study entitled The factors Affecting Perceived Organizational Effectiveness: The Sangguniang Kabataan Experience in Iloilo City (Nov. 2007-Nov. 2010) aimed to described the profile of the SK in selected barangays in Iloilo City to enumerate and describe the choices of projects of the selected barangays in Iloilo City and determine the effectiveness of SK as an organization using the four criteria namely, the attainment of objectives, technical support, partnerships with other organizations, and cohesion and teamwork, the determination of the significance of the factors affecting the effectiveness of the SK as an organization and discussion of the challenges within the SK management and to proposal of policy interventions that may improve the effectiveness of the SK organization. The Key Informants for this study were the Sangguniang Kabataan Chairpersons (Nov. 2007- Nov. 2010). The study used the Profit Regression Analysis to explain the behavior of dependent variable and Bivariate Analysis to determine the correlation among existing independent variables. The researchers found out that prevalence of conflicts and challenges among the SK Chairperson and the Barangay Council had an effect on the pursuance of the projects of the SK, most barangays near the center of the city and who had higher populations had the highest annual Internal Revenue Allotment, most of the barangays partnered with fraternities that exist in their community or within the city, low technical support had an impact on the performance and effectiveness of the SK. Further the Profit Regression Analysis also found out that Age and Population Density where significant factors affecting the effectiveness of the SK. The results in this study are not indicative of the real significant relationships between the dependent and independent variables, but instead provide interesting and valuable insights, and is indicative of certain relationships that can be studied further in the studies in the future.